Skills Improvement for Local Integrated Healthcare Post (Posyandu) Cadres and Housewives through Training on Making Healthy Snacks Based on Fisheries Waste in Benda Baru, South Tangerang - Mariani Alitimbul; Guspri Devi Artanti (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
The program aimed at improving the skills of housewives and Posyandu cadres in Benda Baru Village,  South Tangerang Regency in the form of training in making healthy snacks based on fishery waste in the  form of shrimp shells, which is a community service program aimed at 25 housewives and Posyandu cadres.  The expected outcome of the training is an increase in skills as an effort to form / develop a group of people  who are economically independent and prosperous. Outputs in community service are snack products from  fishery waste, modules for healthy snacks based on fishery waste, scientific publications and publications  on activities of making healthy snacks based on fishery waste in the form of a Youtube platform. The method  used in this activity is lectures, demonstrations, and practice together with the training participants to make  healthy snacks using ingredients from fishery waste in the form of shrimp shells. The results of the training  to improve skills in making healthy snacks based on fishery waste were followed well by the participants  by making scallops and salted eggs using flour from shrimp shell waste.